On the larval stages of Macrocoeloma diplacanthum (Decapoda: Brachyura: Majidae), and a review of Mithracine phylogenetic aspects - Marques, Fernando P. L. [UNESP]; Pohle, Gerhard W.; Vrbova, Linda [UNESP] (Oxford University Press (OUP), 2003)
Larval development of Macrocoeloma diplacanthum (Stimpson) consists of two zoeal stages, followed by the megalopa. Each larval stage is described in detail. The duration of the zoeal stages was 2-3 (2.4 ± 0.5) and 3-4 (3.5 ± 0.5) days for the first and second zoea, respectively, the megalopa phase appearing 6-8 (7.0 ± 0.5) days after hatching. Unlike for other majids, zoeal stages of M. diplacanthum can be readily distinguished by their distended forehead with strong underlying muscle bands, undercut dorsal carapace spine, and spine on the terminal endopod segment of the first maxilliped. No other known mithracine or majid zoeae exhibit this combination of features. Our zoeal account of M. diplacanthum from Mexico is remarkably consistent with Floridian specimens previously described. However, we have found some differences between descriptions, which could be attributed to natural variation or inadequate description. Previous attempts to evaluate the relationships within Mithacinae have been based on larval characters widely distributed throughout Majidae and therefore are considered inadequate to infer sister-group relationships. The phylogenetic analysis of majids suggested that the position of Mithracinae is still uncertain, as is its monophyletic status. We recommend that additional characters, particularly of the megalopa phase, be sought for a better resolution of majid evolutionary history.